Identification of a novel mutation (p.Ile198Thr) in gene TYR in a Pakistani family with nonsyndromic oculocutaneous albinism. (1st July 2014) - Shah, S. A.; Din, S. U.; Raheem, N.; Daud, S.; Mubeen, J.; Nadeem, A.; Tayyab, M.; Baloch, D. M.; Babar, M. E.; Ahmad, J.
Summary: The TYR gene (MIM #6069333) is located at position 11q14.3 on the human chromosome, and encodes tyrosinase, which is expressed in melanocytes and controls the biosynthesis of melanin. Most TYR mutations eliminate the activity of tyrosinase, preventing melanocytes from producing any melanin throughout life. People with this form of albinism have white hair, light‐coloured eyes and very pale skin. Some mutations in TYR reduce but do not completely eliminate tyrosinase activity, and allow some melanin to be produced. We report a Pakistani family with four members affected by oculocutaneous albinism (OCA). Blood samples were collected from all affected individuals, normal siblings and their parents. Genomic DNA was extracted, and sequence analysis of all the coding exons and adjacent intronic sequences of TYR was performed, which identified a novel missense substitution (p.Ile198Thr). Sequencing of TYR in 90 unrelated healthy individuals showed no sequence variant at this location. Our study expands the mutational spectrum of OCA1.